Outcomes from an extended scope of practice speech-language pathology service for low risk ENT outpatients: A 5-year service review. (2nd January 2022) - Schwarz, Maria; Ward, Elizabeth C.; Seabrook, Marnie; Davis, Jennifer; Whitfield, Bernard C. S.
Abstract: Purpose : Early evidence supports the safety and efficiency of extended scope speech-language pathology (SLP) clinics designed to manage low risk ear nose and throat (ENT) outpatient referrals, however long-term data is lacking. The aim of this study was to complete a 5-year audit of clinical outcomes, including rates of re-referral, for a SLP Allied Health Practitioner (SLP AHP) led dysphagia and dysphonia service within an Integrated Specialist ENT Service. Method : A retrospective audit was undertaken of all patients referred with non-urgent dysphonia and/or dysphagia symptoms over a 5-year period since establishment of the SLP AHP service. Clinical outcomes, rates and reasons for re-referral to the specialist ENT waiting list were investigated. Result : Of 616 patient referrals, 462 patients were seen by the SLP AHP service. Most (72%, n  = 333) received all required management through the clinical model, with only 28% ( n  = 129) requiring additional ENT intervention, consistent with previously published data. Only 36 of the 616 (6%) were re-referred/re-presented within 12 months of first presentation, of which only 12 were referred for same condition as initial referral. No adverse outcomes were recorded on the clinical database during this 5-year period. Conclusion : Results provide further evidence that the SLP AHP service is a safe and efficient method for managing low risk ENT outpatient referrals.